2020
DOI: 10.7759/cureus.7886
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Routine Hematological Parameters with In-hospital Mortality and Length of Hospital Stay in Patients with Large Middle Cerebral Artery Infarction

Abstract: Neutrophil-to-lymphocyte ratio (NLR) and red blood cell distribution width (RDW) reflect inflammation and these parameters have not been studied in patients with large cerebral artery infarction. This study investigated the correlation of these inflammation parameters with inhospital mortality and length of hospital stay (LOS) in patients with large middle cerebral artery (MCA) infarction. Materials and methods The study was conducted with patients who had large MCA (M1 and M2 segments) infarction. Clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In the present study, we found that in addition to the LDL-C to lymphocyte ratio, RDW-SD predicts mortality in patients with ACI. This result is consistent with that of previous studies [ 5 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we found that in addition to the LDL-C to lymphocyte ratio, RDW-SD predicts mortality in patients with ACI. This result is consistent with that of previous studies [ 5 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, investigators have been focusing on new and effective prognostic factors relating to ACI. In recent studies, hematological parameters, such as neutrophil to lymphocyte ratio [ 5 ], monocyte to high-density lipoprotein cholesterol (HDL-C) ratio [ 6 ], C-reactive protein to albumin ratio [ 7 ], red blood cell distribution width (RDW) [ 8 ], and the neutrophil to eosinophil ratio [ 9 ], were found to be associated with the prognosis of ACI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These found that RDW is associated with 1-month mortality in patients with malignant middle cerebral artery infarction 19 and that high RDW is a poor prognostic factor. 20 However, to our knowledge, there is no study on the relationship between RDW and the prognosis of the stroke subtype—SAO. Moreover, previous studies investigated the prognostic indicators of mortality and poor function, but there were no studies related to recurrence.…”
Section: Introductionmentioning
confidence: 98%